Comparación de tres métodos de cuantificación de la carga de entrenamiento en baloncesto. [Comparison of three methods of quantifying the training load in basketball]. - María Reina; David Mancha-Triguero; David García-Santos; Javier García-Rubio; Sergio J. Ibáñez (Ramón Cantó Alcaraz, 2019)
For proper training planning, it is necessary to know how the efforts are distributed throughout the week and, therefore, to evaluate the load support by the athletes. With this mission, the use of intelligent devices to control the training load is booming. As it is a costly method, it is important to pay attention to measures that involve a lower cost. The objective of this study was, first, to quantify the training load through the types of instruments, in order to establish relationships between them. The tasks were analyzed by inertial devices, heart rate bands and a training record sheet. Second, establish whether there is a direct relationship between the measurements used. Thus, the design of the present study fits into correlational research. The training of a women's basketball team was analyzed ecologically, without intervening in the sessions, collecting a total of 120 tasks. The obtained results affirm that there is a statistically significant correlation between the three types of load measurement during the same training tasks, mainly between the load established by the inertial devices and the record sheet used (r =, 897; r2 =, 804). The evaluation of the training load did not differ according to the measure of collection of information used. Using a record sheet, which does not imply any cost, it is informed about the real load supported by the athletes during the training.